Aplikasi Pewarnaan Graf dengan Algoritma Recursive Largest First pada Penjadwalan Mata Kuliah - Rahmat Syam; Hisyam Ihsan; Asman (Journal of Mathematics, Computations and Statistics, 2019)
This research discusses the colorization of graph vertex using algorithm of Recursive Largest First (RLF) in scheduling courses in one of the study programs at one of the universities in Makassar. Representation of problems in scheduling courses was done by making it in the shape of the graph assuming subjects as vertex and the presence of the same lecturers teach different courses as a side. The steps in solving a problem that was mapping the lectures data, representing the lectures data as a graph, forming adjacency matrix, coloring the graph vertex using algorithm of RLF, so that the schedule was retrieved. Scheduling of courses using the colorization of graph vertex with algorithm of RLF as well as the help of VBA for Microsoft Excel 2016 at Faculty of Animal Husbandry obtained 102 vertices with 25 colors indicates that it takes 25 of lecture schedules. The number of vertices that were colored with the same color ≤ 6 vertices meaning in every slot needed 6 lecture rooms in maximum. Scheduled courses are guaranteed that no schedule conflicts for each lecturer of courses taught.